The participation of ascorbic acid in the respiration of the lemon (Revista Española de Fisiología, 1965)
The enzyme ascorbic acid: O2 oxydoreductase is present in large amounts in young lemons. The existence of an electron transport system from malic acid to oxygen, mediated by NADP, glutation and ascorbic acid is studied. Essays in Thumberg tubes show that malic acid is oxydized by glutation and catalytic amounts of NADP. Manometric methods show that glutation can be enzymically oxydized by oxygen and catalytic amounts of ascorbic acid. Seasonal variations are found for the operation of the total system.